Tumor suppressor p73 induces apoptosis of murine peritoneal cell after exposure to hydatid cyst antigens; a possibly survival mechanism of cystic echinococcosis in vivo mice model. - Ehsan Ahmadpour; Adel Spotin; Ata Moghimi; Firooz Shahrivar; Farhad Jadidi-Niaragh; Farnaz Hajizadeh; Sirous Mehrani; Komeil Mazhab-Jafari (PLoS ONE, 2023)
Cystic echinococcosis (CE) is a life-threatening helminthic disease caused by the Echinococcus granulosus sensulato complex. Previous evidence indicates that the host's innate immune responses against CE can combat and regulate the growth rate and mortality of hydatid cyst in the host's internal organs. However, the survival mechanisms of CE are not yet fully elucidated in the human body. In the present study, the apoptotic effects of fertile and infertile hydatid fluid (HF) were tested on murine peritoneal cells in vivo mice model. Mice were divided into five groups including; control group, fertile HF-treated peritoneal cells, infertile HF-treated peritoneal cells, protoscolices (PSCs)-treated peritoneal cells and HF+PSCs-treated peritoneal cells group. Mice groups were intraperitoneally inoculated with PBS, HF, and/or PSCs. Afterwards, peritoneal cells were isolated and mRNA expression of STAT3, caspase-3, p73 and Smac genes were evaluated by quantitative Real-time PCR. After 48 hours of exposure, the protein levels of Smac and STAT3 was determined by western blotting technique. After 6 hours of exposure, Caspase-3 activity was also measured by fluorometric assay. The intracellular reactive oxygen species (ROS) production was examined in all groups. The mRNA expression levels of p73, caspase-3 and also Caspase-3 activity in HF+PSCs-treated peritoneal cells were higher than in the test and control groups (Pv<0.05), while the mRNA expression level of anti-apoptotic STAT3 and Smac genes in HF+PSC-treated peritoneal cells were lower than in the other groups (Pv<0.05). As well, the level of intracellular ROS in the fertile HCF-treated peritoneal cells, infertile HCF-treated peritoneal cells, PSC-treated peritoneal cells and HF+PSC-treated peritoneal cells groups were significantly higher than in the control group (Pv<0.05).Current findings indicates that oxidative stress and p73 can trigger the apoptosis of murine peritoneal cells through modulator of HF-treated PSCs that is likely one of the hydatid cyst survival mechanisms in vivo mice model.